Exosomal Lipids in Cancer Progression and Metastasis - Dandugudumula Ramu; Eunjoo Kim (Cancer Medicine)
ABSTRACT Background Metastasis is the primary cause of cancer mortality. It is responsible for 90% of all cancer‐related deaths. Intercellular communication is a crucial feature underlying cancer metastasis and progression. Cancerous tumors secrete membrane‐derived small extracellular vesicles (30–150 nm) into their extracellular milieu. These tiny organelles, known as exosomes, facilitate intercellular communication by transferring bioactive molecules. These exosomes harbor different cargos, such as proteins, nucleic acids, and lipids, that mediate multifaceted functions in various oncogenic processes. Of note, the amount of lipids in exosomes is multifold higher than that of other cargos. Most studies have investigated the role of exosomes' protein and nucleic acid content in various oncogenic processes, while the role of lipid cargo in cancer pathophysiology remains largely obscure. Materials and Methods We conducted an extensive literature review on the role of exosomes and lipids in cancer progression, specifically addressing the topic of exosomal lipids and their involvement in cancer metastasis and progression. Conclusions This review aims to shed light on the lipid contents of exosomes in cancer metastasis. In this context, the role of exosomal lipids in signaling pathways, immunomodulation, and energy production for cancer cell survival provides insights into overcoming cancer progression and metastasis.